Influence of granular activated carbon media properties on natural organic matter and disinfection by-product precursor removal from drinking water. (1st May 2020) - Golea, D.M.; Jarvis, P.; Jefferson, B.; Moore, G.; Sutherland, S.; Parsons, S.A.; Judd, S.J.
Abstract: Operational and financial constraints challenge effective removal of natural organic matter (NOM), and specifically disinfection by-product (DBP) precursors, at remote and/or small sites. Granular activated carbon (GAC) is a widely used treatment option for such locations, due to its relatively low maintenance and process operational simplicity. However, its efficacy is highly dependent on the media capacity for the organic matter, which in turn depends on the media characteristics. The influence of GAC media properties on NOM/DBP precursor removal has been studied using a range of established and emerging media using both batch adsorption tests and rapid small-scale column tests. DBP formation propensity (DBPFP) was measured with reference to trihalomethanes (THMs) and haloacetic acids (HAAs). All GAC media showed no selectivity for specific removal of precursors of regulated DBPs; DBP formation was a simple function of residual dissolved organic carbon (DOC) levels. UV254 was found to be a good surrogate measurement of DBPFP for an untreated water source having a high DOC. Due to the much-reduced concentration of DBP precursors, the correlation was significantly poorer for the coagulation/flocculation-pretreateed water source. Breakthrough curves generated from the microcolumn trials revealed DOC removal and consequent DBP reduction to correlate reasonably well with the prevalence pores in the 5–10 nm range. A 3–6 fold increase in capacity was recorded for a 0.005–0.045 cm 3 /g change in 5–10 nm-sized pore volume density. No corresponding correlation was evident with other media pore size ranges. Graphical abstract: Image 1 Highlights: Impact of GAC media pore size distribution on THM and HAA formation potential, FP. 8 GAC media and both adsorption isotherm & microcolumn tests on raw & treated water. Correlations of capacity vs pore volume across different pore size ranges produced. No selectivity of DBP FP observed for any of the media tested. Strongest correlation of capacity observed for 5–10 nm pore size range.